Bank Rescues and Fiscal Policy in the European Union during the Great Recession - Ferreiro, Jesús; Gálvez, Catalina; Gómez, Carmen; González, Ana (Panoeconomicus, 2016)
The outbreak of the economic and financial crisis in 2008, the so-called Great Recession, has made that many European Union countries have made massive interventions in their banking and financial systems. These interventions have had a considerable impact in the public finances of these countries. The aim of the paper is to analyze the impact on the national public budgets of the measures of public support to problem financial institutions carried out between the years 2008 and 2013, and to study how this budgetary impact has affected to the fiscal imbalances and to the strategies of fiscal impulse and consolidation implemented along these years.Key words: European Union, Fiscal policy, Great Recession, Financial crisis, Bank rescues.JEL: E62, E65, H62, O52.